Analisis Faktor-Faktor yang Mempengaruhi Minat Pedagang Pasar Atas Bukittinggi Menggunakan Pembiayaan Utsman di BPRS Jam Gadang - Santi Handayani; Cahya Agung Mulyana (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research analyzes the factors influencing the interest of traders in Pasar Atas Bukittinggi in using Utsman Financing at BPRS Jam Gadang. This study is motivated by the decreasing number of Utsman Financing customers at the BPRS. Data was gathered through documentation, interviews, and observation using a descriptive qualitative technique. Participants in the study include Pasar Atas Bukittinggi vendors, some of whom have used Utsman Financing services and others who have not. Both internal and external factors impact traders' interest, according to the research. Reasoning and other internal variables, perception, learning, and attitude. Meanwhile, external factors consist of culture, social, and personal factors. The most influential factors are the motivation to avoid riba and a positive perception of Utsman Financing. In terms of external factors, personal factors (economic needs) and social factors (recommendations from the environment) have a significant influence. Cultural factors were found to have a relatively small influence on traders' interest in using Utsman Financing.